The Staff of Ninšubura. Studies in Babylonian Demonology, II - Wiggermann. F. A. M. (1985)
1987; 1. The identification of Ninšubura; 2. A false Ninšubura: "the god with the mace"; 3. The staff of the vizier; 4. The office of the vizier; 6. Sumerian angelology; 6. An alternative identity for the "god with the mace". Bibliography.